Extracellular vesicle-mediated nucleic acid transfer and reprogramming in the tumor microenvironment. (10th July 2020) - Parayath, Neha N.; Padmakumar, Smrithi; Amiji, Mansoor M.
Abstract: Extracellular vesicles (EVs) have garnered much attention as key mediators of intercellular communication within the tumor microenvironment (TME) as well as at distinct metastatic sites. Nucleic acid molecules are the important components of the EV cargo. Characterizing EVs and strategies for modulating the nucleic acid content to promote anti-tumoral functions has led to the emerging role of EVs as potential novel targets for cancer therapy. Recent approaches of engineering the EVs to reach targeted sites have bought this to the forefront for nucleic acid delivery. In this article, we discuss EV biology with recent methods to analyze their nucleic acid contents. We emphasize the role of EV-mediated nucleic acid transfer in the TME assisting in tumor progression and metastasis and further review the strategies for modulating the nucleic acid content in EV for suppressing tumor growth and immune activation. The article further discusses the recent developments in generating EV mimics as nucleic acid delivery systems. Highlights : Tumor extracellular vesicle (EV) biogenesis and nucleic acid content. Role of EV-mediated nucleic acid transfer and cellular reprogramming in the tumor. microenvironment. Strategies to modify EV nucleic acid content for anti-tumor therapeutic effects. EV-mimicking nano-vesicles for tumor targeted delivery of nucleic acid.